ANALISIS FRAMING TENTANG PEMBERITAAN PEMINDAHAN IBU KOTA NEGARA PADA MEDIA ONLINE REPUBLIKA.CO.ID DAN KOMPAS.COM - Meisdanur Azani; Dhanurseto Hadiprashada; Dionni Ditya Perdana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Discussions on moving the State Capital (IKN) in early 2019 became one of the hot topics in the country and media attention in Indonesia. Framing is the framing of information used by a media. The selection of the news portals Republika.co.id and Kompas.com is not without reason. kompas.com occupies the 9th position and Republika.co.id occupies the 34th position, included in the category of the top 50 sites in Indonesia. This research intends to identify the framing of national mass media coverage of the decision to move the State Capital (IKN) to Kalimantan. This research is a type of qualitative descriptive research, using the Zhongdang Pan and Gerald M. Kosicki framing analysis model which has four analytical tools, namely syntax, script, thematic, and rhetorical. Data collection techniques in this research use techniques through primary data and secondary data. This research was conducted through observing online news texts on the media Republika.co.id and kompas.com by selecting 5 stories in each media for the period March to April 2022. Based on the data that has been found from 5 news stories in both media, there are each one news that does not meet the elements of completeness of the news. The comparison of framing in the information that sticks out by Republika.co.id and kompas.com is most often seen in the way the facts are presented and the selection of sources. The results of this study show that Republika.co.id constructs more of a government figure in following up on issues in the process of transferring IKN.